From net effects to configurational pathways: a dual examination of employee innovative behavior through integrated SEM-fsQCA framework - Jiao, Yongji; Cheng, Hai; Huang, Xinyi; Ouyang, Jieyu; Li, Qishu; Wang, Ruirui (Frontiers in Psychology, 2026)
IntroductionWhile conventional structural equation modeling (SEM) emphasizes net effects between variables, it inadequately captures the multiple equifinal pathways underlying employee innovative behavior. Drawing on componential creativity theory and social cognitive theory, this study advances a methodological triangulation approach by integrating SEM with fuzzy-set qualitative comparative analysis (fsQCA) to examine the mechanisms through which trait mindfulness influences innovative behavior.MethodsWe analyzed data from 297 employees in digitally transforming organizations, employing both SEM and fsQCA to test symmetric causal relationships and identify asymmetric configurational patterns.ResultsSEM findings reveal that trait mindfulness affects innovative behavior through work flourishing (full mediation) and organizational resilience (partial mediation), with digital leadership exerting a negative moderating effect. fsQCA identifies three equifinal configurations leading to high innovative behavior, with the “high mindfulness × high resilience” configuration emerging as the dominant pathway.DiscussionThis study demonstrates the methodological complementarity of SEM-fsQCA integration: whereas SEM elucidates symmetric causal relationships and average effects, fsQCA unveils asymmetric configurational patterns and necessary/sufficient conditions, providing a more comprehensive understanding of the complex mechanisms driving employee innovation.